2019
DOI: 10.1002/lary.28256
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of the first cervical nerve does not influence outcomes in upper airway stimulation for treatment of obstructive sleep apnea

Abstract: Objectives/Hypothesis: Upper airway stimulation (UAS) has demonstrated efficacy in the management of obstructive sleep apnea (OSA). Branches of the hypoglossal nerve that selectively activate tongue protrusor and stiffener muscles are included within the stimulation cuff electrode. The first cervical nerve (C1) is often also included to stimulate additional muscles contributing to tongue protrusion and stabilization. The purpose of this study was to determine whether inclusion of the C1 translates into treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A bi-polar stimulator is utilized to identify and assist in separation of these branches. In addition, it is typical that the first cervical nerve branch to the geniohyoid muscle is included in the dissection and ultimately within the stimulation electrode; however, recent data suggest that this may not assist in any additional reductions in sleep apnea postoperatively [27]. Once the nerve branches to the protrusors are identified, the stimulation electrode is wrapped around the branches, and the electrode cuff is held in place via friction and an anchoring site sutured to the digastric tendon.…”
Section: Operative Techniquementioning
confidence: 99%
“…A bi-polar stimulator is utilized to identify and assist in separation of these branches. In addition, it is typical that the first cervical nerve branch to the geniohyoid muscle is included in the dissection and ultimately within the stimulation electrode; however, recent data suggest that this may not assist in any additional reductions in sleep apnea postoperatively [27]. Once the nerve branches to the protrusors are identified, the stimulation electrode is wrapped around the branches, and the electrode cuff is held in place via friction and an anchoring site sutured to the digastric tendon.…”
Section: Operative Techniquementioning
confidence: 99%
“…3). While recommended for inclusion, it has not yet shown additional benefit in OSA treatment [49]. A radiologic study revealed that smaller baseline soft palate volume and greater anterior tongue movement with stimulation improved treatment response to UAS [50].…”
Section: Anatomical Considerationsmentioning
confidence: 99%